The geographical location of retail outlets/ service stations in the Nigerian petroleum industry - M. O. Lawal (Faculty of Geography, Universitas Gadjah Mada, 2005)
This paper examinie the channels of petroleum distribution in Nigeria from the Refineries to Depot and Retail Outlets/Service Stations where the consumers finally purchase their products. Specifically the paper considers some of the geographical factors that are influencing the location of service stations in the Nigerian Petroleum Industry.